The results of experimental studies of the level of vibrational impact on a road sweeping machine’s operator - P. A. Korchagin; I. A. Teterina (Вестник СибАДИ, 2017)
The article dwells upon results of experimental testing vibroprotective system of a road sweeping machine on the basis of the MTZ-80 tractor for different operating modes of the machine. There is presented an analysis of the received acceleration levels, during experiment, on the internal combustion engine’s frame and a workplace of a road sweeping machine’s operation. The most vibroloaded operation mode is determined.